Diagnostic of hygienic sanitary conditions in cheeses factories: a review (Research, Society and Development, 2021)
Cheeses manufactured by hand may be more likely to be contaminate if they are produced with raw materials that are not safe. For this reason, it is important that companies adopt the implementation of manufacturing and quality control programs, so that the risk of contamination is reduced, in addition to ensuring that it is produced with quality raw material and the process follows all current regulations to have a safe final product. With this in mind, this research aimed to understand the quality control and cheese making, through a bibliographic review. Five national articles related to the hygienic-sanitary conditions of cheesemakers were compared in databases such as Scielo, Pub Vet, Legislative Portal of Ministry of Agriculture, Livestock and Supply, website of the Nacional Health Surveillance Agency and the Portal da Embrapa and in published books, between the years 2010 and 2020. This comparison, showed that most establishments did not have any type of inspection and did not carry out activities in accordance with current legislation. Thus, it can be seen that the cheeses produced were of low quality.